Effects of coagulant morphology and chemical properties on soluble reactive phosphate removal in corn ethanol wastewater. (6th August 2021) - Mancuso, Chandler; Jamison, Megan; Zaporski, Jared; Yang, Ziming
Abstract: As ethanol production continues to rise around the world, and wastewater discharge requirements for phosphorus become more stringent, it is important that phosphorus removal technologies are evaluated on ethanol wastewater streams. In this study, five coagulating agents with distinct characteristics were evaluated for their soluble reactive phosphate (SRP) removal performance on both a synthetic wastewater sample and a wastewater sample collected from a corn ethanol manufacturer. All coagulants demonstrated a positive correlation between coagulant dose and percent removal of SRP on both samples. Alum and ferric chloride produced the highest SRP removal efficiencies on both the ethanol and synthetic wastewater, indicating that prepolymerized, high‐basicity coagulants (e.g., aluminum chlorohydrate, poly‐aluminum ferric chloride) are less effective for SRP removal than nonpolymerized coagulants. The background matrix analysis combined with the pH studies revealed that the high alkalinity in the ethanol wastewater has a substantial inhibitory effect on SRP removal capacity that supersedes pH effects. These experimental results suggest that the Al‐Al and Al‐OH bonds in the heavily hydroxylated and polymerized structure of high‐basicity coagulants are very rigid, which could prevent inner‐sphere complexation and drive a less effective outer‐sphere interaction, thus hindering SRP removal efficiency. Practitioner points: Five different coagulants are evaluated for reactive phosphate removal from wastewater. Alum and ferric chloride show higher removal efficiency than prepolymerized and high‐basicity coagulants. Optimal removal pH increases with increasing coagulant basicity. Abstract : This study compared the removal efficiency of soluble reactive phosphate (SRP) between polymeric and non‐polymerized coagulants in ethanol plant wastewater. The effects of pH, dose, basicity of coagulant, and addition order on the removal efficiency were examined and discussed.